Passport Skill Assisted Project Based Learning to Improve the Punctuality of Time and Product Quality of Three Dimensional Craft - Riyatmoko, Joko; Rohidi, Tjetjep Rohendi; Utomo, Udi (Universitas Negeri Semarang, 2018)
The inaccurate timing of task collection and the low quality of 3D craft products is due to the fact that most of the students have not been able to manage the timely completion of tasks and lack of optimal control over the tasks assigned. This study aims to determine whether the use of passport skills in project-based learning can improve the timeliness and quality of 3D craft products. An action research conducted in class X Animation 2 SMK N 11 Semarang is done in 2 cycles. Each cycle consists of planning, implementation, observation, and reflection on project based learning with applied passport skill. The data were taken in the form of the timeliness of task collection and product quality measured from the aspect of tidiness, proportion, and uniqueness. The data obtained were analyzed in descriptions. The results show that project-based learning through passport skills can improve the timeliness of X-Animation students of SMK Negeri 11 Semarang. It is proven that students who submitted the task on time rose from 75% to 92%. The learning also improves the quality of three-dimensional craft products, proven by the average in cycle I of 74.31 increased to 85.19. Percentage of completeness in the first cycle reached 64% and in the second cycle increased to 92%. The level of tidiness in cycle I reached 83% increased to 88%, while the proportion aspect increased from 78% to 86%, and the uniqueness aspect increased from 62% to 81%. It was concluded that project-based learning using passport skill enhances the timeliness and quality of 3D craft products in students of X-Animation class of SMK N 11 Semarang.